The Spillover Effects of Affirmative Action on Competitiveness and Unethical Behavior - Ritwik Banerjee; Nabanita Datta Gupta; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2016)
We conduct an artefactual field experiment to examine various spillover effects of Affirmative Action policies in the context of castes in India. We test a) if individuals who compete in the presence of Affirmative Action policies remain competitive in the same proportion after the policy has been removed, and b) whether having been exposed to the policy generates unethical behavior and spite against subjects from the category who has benefited from the policy. We find that these policies increase substantially the confidence of the lower caste members and motivate them to choose significantly more frequently a tournament payment scheme. However, we find no spillover effect on confidence and competitiveness once Affirmative Action is withdrawn: any lower caste's gain in competitiveness due to the policy is then entirely wiped out. Furthermore, the strong existing bias of the dominant caste against the lower caste is not significantly aggravated by Affirmative Action.
Keywords: C70; C91; J16; J24; J31; M52; 330; affirmative action; castes; competitiveness; unethical behavior; field experiment